2006
DOI: 10.1093/geront/46.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Just for Us: An Academic Medical Center–Community Partnership to Maintain the Health of a Frail Low-Income Senior Population

Abstract: Just for Us is becoming a financially sustainable way of creating a "system within a nonsystem" for low-income elderly persons in clustered housing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…The same assistant contacts the patient after the visit and before the next visit. 61 Phelan et al 63 found that a interdisciplinary geriatric team model screened for more syndromes and improved care at 12 months, although there was little significant improvement thereafter. Disease-specific team models produce good results for the focal disease but are less successful with comorbidities.…”
Section: Supporting Literaturementioning
confidence: 99%
“…The same assistant contacts the patient after the visit and before the next visit. 61 Phelan et al 63 found that a interdisciplinary geriatric team model screened for more syndromes and improved care at 12 months, although there was little significant improvement thereafter. Disease-specific team models produce good results for the focal disease but are less successful with comorbidities.…”
Section: Supporting Literaturementioning
confidence: 99%
“…For example, the Duke University program "Just for Us" provides care for seniors with chronic and complicated medical conditions. 33 The team is led by a physician and includes PAs (who get paid through the local federally qualified health center), social workers (provided through county services), case workers (paid through the "Just for Us" program and the insurer), and a dietitian (paid through private insurance and Medicaid). Medical care is coordinated by the patient's PCP.…”
Section: Team-based Approaches For Diabetes Carementioning
confidence: 99%
“…46 Furthermore, Dr. Lloyd Michener encouraged ingesting community-level data ("community vital signs") into EHRs to better understand a patient's neighborhood context and potentially to guide the development of coordinated, multisectoral interventions. 47,48 For example, the Just for Us program was launched after identifying increased needs of elderly patients in low-income housing in Durham, North Carolina 49 , partnering primary care, county health departments, and housing agencies to bridge clinical medicine with public health and social services. Other bright spots that were highlighted include documenting patient experiences in the EHR 50 and supplementing monitoring patients' SDHs in the EHR, with social needs identified by community advisory councils.…”
Section: Sdhs In Primary Carementioning
confidence: 99%